2020
DOI: 10.31299/hrri.55.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Podrška škole djeci s teškoćama u ponašanju i učenju iz perspektive roditelja i djece

Abstract: The aim of this paper was to describe perceptions and experiences of school support for pupils with learning and behavioural difficulties from the perspective of parents and their children. Interviews were conducted with 33 participants in 10 families at risk. Inductive thematic analysis showed that the key topic was to explain how behaviour and learning difficulties unnoticed by the school progress to behaviour and learning problems and problems in the family environment. The results suggest that family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…It connects people, yes, and inspires them for their future." (D1/10) However, the boys participating in this study were much more likely to talk about their school experience as a major area of challenge and a place where difficulties arising from the spectrum of ADHD symptoms were most pronounced; this finding is consistent with previous studies on this subject (e.g., Loe and Feldman, 2007;DuPaul and Langberg, 2014;Barkley, 2015;DuPaul and Stoner, 2016;Koller-Trbović et al, 2019). The boys regularly perceived school as being synonymous to burdensome activities associated with education ("… what is hard for me to do?…”
Section: Theme: Challenges Of Schooling With Adhdsupporting
confidence: 87%
“…It connects people, yes, and inspires them for their future." (D1/10) However, the boys participating in this study were much more likely to talk about their school experience as a major area of challenge and a place where difficulties arising from the spectrum of ADHD symptoms were most pronounced; this finding is consistent with previous studies on this subject (e.g., Loe and Feldman, 2007;DuPaul and Langberg, 2014;Barkley, 2015;DuPaul and Stoner, 2016;Koller-Trbović et al, 2019). The boys regularly perceived school as being synonymous to burdensome activities associated with education ("… what is hard for me to do?…”
Section: Theme: Challenges Of Schooling With Adhdsupporting
confidence: 87%
“…Koller-Trbović and Širanović [37] point out that significant interest in the topic of participation of at-risk children has been evident in the Croatian research discourse only in the last fifteen years or so, while the research encompasses several contexts and topics (e.g., the participatory rights of children in educational institutions, of children who are in the process of a needs analysis and intervention planning, who are in foster care, or who are undergoing non-institutional treatment). Even though these are smaller and most often qualitative studies, the results almost unambiguously indicate that children's participatory rights are insufficiently observed and very diversely perceived in practice.…”
Section: Context Of the Researchmentioning
confidence: 99%
“…It may be concluded that the results of key Croatian studies on this topic unequivocally show the children's readiness to participate, but also their continued insufficient involvement and partnership with adults, especially in terms of participating in decisions on their future lives. In direct treatment, children report better opportunities for participation than in the process of needs analysis and intervention planning, even if such opportunities are still insufficient [37]. Therefore, this research was conducted with the aim of deepening the knowledge and understanding of participation of adolescents in various aspects of institutional life.…”
Section: Context Of the Researchmentioning
confidence: 99%
“…In assessing RSE, a child is not observed in isolation “but in the context of the social, and especially, microsocial environment” (Koller-Trbović et al, 2017, p. 12). This involves a process of determining the probability of the unfavorable development of the child to acquire a clearer picture of the needs of children and their families.…”
Section: The Theoretical Framework Of the Studymentioning
confidence: 99%
“…Such an assessment is intertwined with the intervention itself. Contemporary literature considers it a desirable assessment model because it is carried out without removing children from their natural environment, and it provides for dynamism and continuity and for assessing a child’s natural and spontaneous reactions (Koller-Trbović et al, 2017). However, very little is known about the preparedness of ECEC teachers to respond to these requirements and about the possibility of early identification of the RSE of preschool-age children, although different methods of assessing the development and social functioning of children have been developed in the last few decades (Howard & Melhuish, 2017).…”
Section: Introductionmentioning
confidence: 99%